Międzypokoleniowe zróżnicowania w doświadczaniu konsekwencji pandemii COVID-19 - Barczykowska, Agnieszka; Pawełek, Katarzyna (Studia Edukacyjne, 2021)
The aim of the article is to present the characteristics of modern generations (Builders, Baby Boomers, Generation X, Millennials – Generations Y, Z and Alpha) and their divergent experience of the COVID-19 pandemic. The methodology involved a review and critical analysis of Polish and English literature of the subject and available reports. The analyses indicate that each generation, to varying degrees, has faced the problem of coping with losses in behavioral, biological, psychosocial, and material terms.